Descartes and Popper on the foundations of knowledge / Mohd Khairul Anam Che Mentri - Mohd Khairul Anam, Che Mentri (2011)
This study attempts to examine the philosophical experiments of Descartes and of Popper in dealing with the problem of the foundations of knowledge. It analyses and presents their instruments and tools, concepts and methods of thinking that they have developed in their struggle to provide answers to such problems. Apart from presenting those experiments separately, this study also narrates in comparative manner the differences and similarities that can be found in their epistemological principles and methods. Conceptually, I divide the study into three major themes. The first theme deals with the historical dimension. In order to throw light on the philosophical ideas of Descartes and Popper, I reconstruct the context in which those ideas emerge by relating them to certain significant episodes in their lives. The presentation of this historical study can be found in Chapter 2 on Descartes, and in Chapter 4 on Popper. Without critical comment, but more as a philosophical exposition, the second theme explains and examines the philosophical thought of Descartes and Popper in dealing with the problem of knowledge and its foundations—of which can be found in Chapter 3 on Descartes’, and in Chapter 5 on Popper’s. In the course of this exposition, I endeavour to provide a systematic reconstruction of their epistemological systems and their specific views on the foundations of knowledge, and in certain places suggest some new interpretations. The last theme deals, in a comparative manner, with some fundamental differences and striking similarities in their epistemological principles and methods. The main conclusion which I reach is that there exist similar approaches, but with different instruments or conceptions or methods and ultimately they bring forth strikingly different results.